Caracterização físico-química, carotenoides totais e elementos-traço em cenoura (Daucus carota L.) e tomate (Lycopersicon esculentum) orgânico e convencional - Valéria da Silva Pereira (2014)
Organic leafy vegetables insertion programs in the school nutrition produced by family farms have been implemented in Brazil as a strategy of nutrition security and nourishment and sustainable local development. Food raised in different systems of agricultural production, conventional and organic, can present differences in quantity and variations in their chemical composition. In this way, this work aims to compare the physio-chemical composition, to determine the the proportion of total carotenoids and the trace elements of samples of carrots (Daucus carota) and tomatoes (Lycopersicon esculentum), organic and conventional. The organic samples were acquired from family farms from Capim Branco-MG and the conventional were acquired in CEASA/MG. It was developed a physio-chemical characterization using official methods, it was analyzed pH, titratable acidity, total soluble solids, relationship Brix / acidity, reducing sugars, non-reducing and total and chemical composition of the sample (moisture, protein, lipid, total ash, minerals, dietary fiber and carbohydrates by difference). Trace elements and total carotenoids, the last one just in the carrot matrix, were determined by mass spectrometry with inductively coupled plasma and ultraviolet spectrophotometry, using validated methods. It was proved, by parameters of performance studied, that this method is suitable for the spectrophotometric method in quantifying total carotenoids in carrot. The organic samples of carrots and tomatoes showed high levels of ph and total sugar proportions, and less acidity when compared to inorganic (p < 0,05), indicating a better sensory profile of organic products. In relation to their composition there was no considerable difference to the products from different production systems (p > 0,05), with the exception of moisture in carrots and tomatoes and ashes only to carrots (p < 0,05). In respect to the trace elements, differences in As and Cd contents were identified only in conventional samples, due to, probably, the use of pesticides and phosphate fertilizers; on the other hand, higher levels of zinc were identified in organic vegetable crops. The organic carrot presented a higher Mn content and tomato greater copper content. It was not noticed difference in the proportion of total carotenoids in organic carrot and conventional (p > 0,05). The sum of the observed results allowed not establishes if the different production systems influence the nutritional quality of vegetable crops. However, due to high pH value, less acidity and an increased proportion of sugar identified in organic production carrot and tomato, it can be inferred that those leafy vegetables are probably more tasteful and well accepted by the population.